APPLICATION OF SCIENTIFIC APPROACH WITH REALIA MEDIA IN INCREASE OF NATURAL SCIENCE LEARNING FOR ELEMENTARY SCHOOL FIFTH GRADE STUDENT - Rokhmah, Anik Nur (KALAM CENDEKIA PGSD KEBUMEN, 2018)
Abstract: Application of Scientific Approach with Realia Media in Increase of Natural Science Learning for Elementary School Fifth Grade Student. The objectives of the research are: (1) to describe the steps of scientific approach with realia media, (2) to describe the improvement of natural science learning about force, and (3) to describe the problems and solutions. This study is a Collaborative Classroom Action Research that was conducted in three cycle. Each cycle consists of planning, implementation, observation, and reflection.  The subjects of this research was 23 students of SD Negeri 2 Banjurpasar. The results show that the application of scientific approach with realia media that implemented with appropriate procedure can improve natural science learning about force at the fifth grade students. Keywords: Scientific approach, realia media, learning, natural science